How to Plagiarize and Not Lose Originality. Bakhtin’s Dialogical Discourse and the Statute of the Bastard - In Memory of Réjean Ducharme - Vianna Neto, Arnaldo Rosa (2018)
This article discusses the additional condition of the theoretical elaboration of literary discourse in the Bakhtinian multidimensional and interdisciplinary concept, that is, the construction of a relational discourse, or a poetics of the intertextual relation in the work of the writer Réjean Ducharme. Hyphenated as Canadian-French, Ducharme is given the identity statute of bastard, and is allowed or metaphorically authorized to devour and plagiarize in the practice of intertextual operations, such as citation, parody, recycling, and patchwork.